Occlusal wear pattern during sleep in adolescents aged 12 to 17 years according to Angle’s classification - Noy-Baquero, Nicolás Esteban; Puentes-Riveros, Michel Andrés; Tanaka-Lozano, Eliana Midori (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: the goal of this study was to describe the sleep bruxism-related occlusal wear pattern in adolescents aged 12 to 17 years with full permanent dentition, according to Angle’s molar classification (AMC). Methods: Descriptive cross-sectional study. Prior informed consent, 45 adolescents grouped into Angle I, II, and III molar classification were evaluated. The clinical form was filled out and an alginate impression of the upper arch was obtained and poured with type III plaster, (Orthoprofessional Dental, Colombia), then thermomoulding two Bruxchecker® mouthguards which were provided to the patients with instructions for use (Biostar, Scheu Dental Technology, Germany) . Through visual examination, a practitioner determined the occlusal pattern according to the dental wear produced during mandibular dynamics in sleep, taking into account the location and extension of the markings by reduced red ink in the Bruxchecker®. Results: the total distribution of the sample (n = 45) yielded a higher frequency of two occlusal patterns: group function with balanced contact points (GF + BCP: 35.6%) and group function with balanced contact areas (GF + BCA: 24.4%). Conclusions: the distribution of occlusal wear patterns for AMC I showed predominance of canine guidance with balanced contact areas (CG + BCA) and canine guide with balanced contact points (CG + BCP) in 53.3%. In AMC II, the predominant patterns (with 80%) were group function with balanced contact areas (GF + BCA) and group function with balanced contact points (GF + BCP). In AMC III, the predominant patterns (with 60%) were group function with balanced contact areas (GF + BCA) and group function with balanced contact points (GF + BCP).